2018
DOI: 10.3390/w10111530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aeration Modes and COD/N Ratios on Organic Matter and Nitrogen Removal in Horizontal Subsurface Flow Constructed Wetland Mesocosms

Abstract: A series of mesocosm-scale horizontal subsurface flow constructed wetlands (HSSF-CWs) were established. In Experiment 1, four artificial aeration (AA) modes, including pre-aeration at 24 h before the input of influent water (PA), aeration at 6 h (6AA) and 12 h (12AA) after the input of influent water and non-aeration (NA), were tested to obtain an optimal aeration mode for chemical oxygen demand (CODCr) and nitrogen removal. The results showed that aeration after the input of influent water could improve the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…It is known that nitrification takes place in aerobic conditions and 1 kg nitrogen removal requires 4.5 kg of oxygen, while 1 kg BOD removal requires 1.2 kg of oxygen (Tchobanoglous and Burton 1991). Further, Chen et al (2018) observed that the nitrification process occurs when dissolved oxygen (DO) in wastewater is above 1.5 mg/L and de-nitrification takes place efficiently when DO is below 0.5 mg/L, but it is difficult to maintain these conditions naturally; hence, artificial aeration is suitable. According to Ye et al (2012), artificial aeration requirement is less in VFCW since 50% of the oxygen is provided by atmospheric oxygen.…”
Section: Intermittent Aeration/artificial Aerationmentioning
confidence: 99%
“…It is known that nitrification takes place in aerobic conditions and 1 kg nitrogen removal requires 4.5 kg of oxygen, while 1 kg BOD removal requires 1.2 kg of oxygen (Tchobanoglous and Burton 1991). Further, Chen et al (2018) observed that the nitrification process occurs when dissolved oxygen (DO) in wastewater is above 1.5 mg/L and de-nitrification takes place efficiently when DO is below 0.5 mg/L, but it is difficult to maintain these conditions naturally; hence, artificial aeration is suitable. According to Ye et al (2012), artificial aeration requirement is less in VFCW since 50% of the oxygen is provided by atmospheric oxygen.…”
Section: Intermittent Aeration/artificial Aerationmentioning
confidence: 99%
“…The earliest full-scale and outdoor pilot-scale aerated treatment wetland systems received continuous (24 h/d) aeration [3,19,20,26,[49][50][51]. Many bench-scale and pilot-scale research studies have investigated the use of intermittent aeration [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. Intermittent aeration via windmill-powered air pumps has also been tested [66].…”
Section: Research Trendsmentioning
confidence: 99%
“…The COD data, after treatment, fulfilled the regulations of the European Union for protection of water quality for discharge into lakes (COD; <125 mg/L). These results may be due to the greater presence of oxygen (Table 1) in systems with vegetation where the greatest COD reductions in CWs were presented after treatment [39]. The COD parameters indicate the ability to reduce oxygen present in receiving bodies of water and are the main parameters for measuring the content of organic matter in wastewater [40,41].…”
Section: Contaminants Concentration In Influents and Effluents From Cwsmentioning
confidence: 99%